Selection of Superior Potato (Solanum tuberosum L.) by Combined Stability Analysis for Future Breeding Strategies - Maulana Haris; Widaningsih Nina Agusti; Kusmana; Jaenudin Usep; Utami Dwinita Wikan; Akhdiya Alina; Handayani Tri; Karjadi Asih Kartasih; Maharijaya Awang; Sobir; Roostika Ika (Agriculture)
Potato is one of the main agricultural commodities and has high economic value. Yield is a trait that becomes a benchmark for user (industry and farmers) in selecting and developing varieties. The selection of superior newly potato somaclones using combined analysis and sustainability index (SI) is still underreported. This study aimed to identify the effect of genotype by environment (growing season) interactions (GEIs), as well as to select superior potato somaclones. The research was conducted in three years (2020 ‒ 2022) in Lembang, West Java, Indonesia. There were 38 somaclones tested in the field, consisting of 37 gamma ray-derived somaclones and one control genotype. The somaclones originated from commercial varieties Agria, Granola, Repita, and Vega. The field trial used a randomized block design that was repeated three times in each year. GEIs were calculated based on a combined ANOVA. Yield stability was assessed using the combined analysis (parametric and non-parametric), genotype plus genotype by environment interaction (GGE) biplot, and sustainability index (SI). Potato somaclones (G), seasons (E) and GEIs were found to have highly significant influence on yield (P < 0.01). According to the combined ANOVA, the GEIs impact accounted for 37.38% of the yield’s total sum of squares. Combining parametric and non-parametric measurements, seven somaclones, P3, P4, P5, P6, P8, P9, and P26, were selected. GGE biplot selected five stable somaclones, namely P3, P4, P22, P23, and P26, while SI selected eight high-yielding and stable somaclones, namely P3, P4, P5, P8, P13, P16, P26, and P32. Based on various stability measurements, three genotypes have been identified as the superior somaclones, namely P3, P4 and P26. This analysis can assist in selecting activities to determine superior somaclones.